Pengaruh Meningkatkan Daya Saing (Sumber Daya Manusia, Infrastruktur, Lingkungan Kerja) Terhadap Perguruan Tinggi Islam di Sekolah Tinggi Agama Islam (STAI) An-Nadwah Kuala Tungkal - Muhammad Muhammad; Maisah Maisah; Fadlilah Fadlilah (Jurnal Ilmu Manajemen Terapan, 2023)
This article discusses and analyzes the influence of education, training, and transfers on teacher career development, as additional insight for faculties and study programs. This literature review article writing method uses library research methods from online media such as Google Scholar, Mendeley and/or other academic online media. The results of this article are: 1) Human Resources influence Islamic Higher Education; 2) Infrastructure influences Islamic Higher Education; and 3) The work environment influences Islamic higher education. Apart from these 3 exogenous variables which influence endogenous variables in the placement of subordinates, there are many other factors including training, promotion, competency and work environment.